2021
DOI: 10.1002/pep2.24235
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in protein modifications techniques for the targeting N‐terminal cysteine

Abstract: N-terminal modifications of proteins have garnered the attention of chemical biologists because of their critical roles in numerous cellular processes, including protein translocation, protein structural and metabolic stability, and the regulation of the half-life of proteins by a process known as "N-end rule pathway." In addition, other posttranslational modification processes also depend on the N-terminal signal sequences. Chemical probes are powerful tools that can be used to investigate N-terminal modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 80 publications
0
26
0
Order By: Relevance
“…However, since most globular proteins contain multiple instances of such AAs, this approach often results in off‐target labeling or a heterogeneous product with the attendant problems of impaired folding or functioning of the modified protein. To address this, genetic engineering methods can be utilized to incorporate a unique reactive AA provided this AA is not already present in the protein sequence or exposed to the accessible protein surface, [ 13 ] at a distinct (e.g., N‐terminal) positions, [ 14 ] or if other instances of this AA can be mutagenized without a significant loss of protein function. [ 6,15 ] Still, particularly for PBPs, for which sequence complexity is usually low, the identification or addition of a unique reactive AA is more probable, unless the fusion of another protein/s or peptide/s to the PBPs is desired (which can reintroduce AA heterogeneity).…”
Section: Strategies For Protein Conjugationmentioning
confidence: 99%
“…However, since most globular proteins contain multiple instances of such AAs, this approach often results in off‐target labeling or a heterogeneous product with the attendant problems of impaired folding or functioning of the modified protein. To address this, genetic engineering methods can be utilized to incorporate a unique reactive AA provided this AA is not already present in the protein sequence or exposed to the accessible protein surface, [ 13 ] at a distinct (e.g., N‐terminal) positions, [ 14 ] or if other instances of this AA can be mutagenized without a significant loss of protein function. [ 6,15 ] Still, particularly for PBPs, for which sequence complexity is usually low, the identification or addition of a unique reactive AA is more probable, unless the fusion of another protein/s or peptide/s to the PBPs is desired (which can reintroduce AA heterogeneity).…”
Section: Strategies For Protein Conjugationmentioning
confidence: 99%
“…[93] Using a solid support approach it was shown that aldehydes in particular can undergo an 'explosion' of diversity from one precursor into many different structures (including olefins, alkynes, amides, amines, β-hydroxyand β-aminoketones, and diverse heterocycles). [94] N-terminal cysteines also offer possibilities for further modification, [95] with native chemical ligation being an obvious example that can be used to attach diverse thioester precursors to the N-terminus. [96] Nitrile-based reagents also provide an option for clean N-terminal modification in proteins and should be compatible with mRNA display, for example cyanobenzothiazoles [97] (although some sequence-specific reactions with other cysteines are possible and cannot be neglected in a peptide library setting).…”
Section: Other Chemistries Not Yet Demonstrated In Mrna Display Using...mentioning
confidence: 99%
“…N ‐terminal cysteines also offer possibilities for further modification, [95] with native chemical ligation being an obvious example that can be used to attach diverse thioester precursors to the N ‐terminus. [96] Nitrile‐based reagents also provide an option for clean N ‐terminal modification in proteins and should be compatible with mRNA display, for example cyanobenzothiazoles [97] (although some sequence‐specific reactions with other cysteines are possible and cannot be neglected in a peptide library setting).…”
Section: Chemistry Compatible With Nucleic Acid Tagsmentioning
confidence: 99%
“…Reactions that are specific to N-terminal Cys residues have been used for site-specific protein labeling, protein semisynthesis, and peptide cyclization. One reaction that has been widely used is the native chemical ligation (NCL), , which proceeds through transthioesterification of N-terminal Cys and subsequent S-to-N acyl exchange . Another reaction relying on selective thiazolidine formation between aldehyde and 1,2-aminothiol has also been widely used, which however takes long reaction times under acidic conditions .…”
Section: Introductionmentioning
confidence: 99%